2023
DOI: 10.1007/s00359-023-01662-6
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanism of circadian clock-based photoperiodism in insects and snails

Yoshitaka Hamanaka,
Masaharu Hasebe,
Sakiko Shiga

Abstract: The photoperiodic mechanism distinguishes between long and short days, and the circadian clock system is involved in this process. Although the necessity of circadian clock genes for photoperiodic responses has been demonstrated in many species, how the clock system contributes to photoperiodic mechanisms remains unclear. A comprehensive study, including the functional analysis of relevant genes and physiology of their expressing cells, is necessary to understand the molecular and cellular mechanisms. Since Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 157 publications
(237 reference statements)
0
1
0
Order By: Relevance
“…PDF has been identified in many insects as the signaling molecule transmitting the time information from the central circadian clock cells (Renn et al 1999 ; Helfrich-Förster et al 2000 ; Beer et al 2018 ; Petri and Stengl 1997 ; Singaravel et al 2003 ). As mentioned above, PDF has also been found to be involved in photoperiodic responses in a number of insects (Hamanaka et al 2023 ). A recent study showed a co-transcription factor EYES ABSENT (EYA) as the downstream target of PDF linking the circadian clock to photoperiodic regulation in Drosophila (Hidalgo et al 2023 ).…”
Section: Similarities Between Photoperiodic Regulation In Insects And...mentioning
confidence: 95%
See 1 more Smart Citation
“…PDF has been identified in many insects as the signaling molecule transmitting the time information from the central circadian clock cells (Renn et al 1999 ; Helfrich-Förster et al 2000 ; Beer et al 2018 ; Petri and Stengl 1997 ; Singaravel et al 2003 ). As mentioned above, PDF has also been found to be involved in photoperiodic responses in a number of insects (Hamanaka et al 2023 ). A recent study showed a co-transcription factor EYES ABSENT (EYA) as the downstream target of PDF linking the circadian clock to photoperiodic regulation in Drosophila (Hidalgo et al 2023 ).…”
Section: Similarities Between Photoperiodic Regulation In Insects And...mentioning
confidence: 95%
“…Both involve the conversion of serotonin to melatonin as an initial step to break diapause, but the photoperiodic pathway uses the day length measure of the circadian clock, while the non-photic pathway is triggered by environmental factors such as temperature. Downstream, a number of species-dependent neuroendocrine pathways are involved, with pigment dispersing factor (PDF) as one common main factor conveying the photoperiodic information (Colizzi et al 2023a , b ; Hamanaka et al 2023 ).…”
Section: Similarities Between Photoperiodic Regulation In Insects And...mentioning
confidence: 99%
“…For seasonal adaptation, a large number of insects inhabiting temperate zones alter their physiological states for development or diapause according to photoperiod. The mechanisms underlying insect photoperiodic responses include photoreceptors, photoperiodic clocks, photoperiodic counters, and endocrine systems (Saunders, 2002;Shiga 2023;Hamanaka et al 2023).…”
Section: Introductionmentioning
confidence: 99%